SAT0030 Higher angiotensin II receptor type 1 (AGRT1) expression and lymphatic vasculature rarefaction in progressive pulmonary parenchymal remodeling of systemic sclerosis patients. (23rd January 2014) - Parra, E.R.; Ruppert, A.D.P.; Capelozzi, V.L.
Abstract : Background: Many proliferative receptor activation and vascular involvement are frequent in systemic sclerosis (SSc), but the role of the specific receptors such as angiotensins II type 1and 2 and lymphatic vasculature are poorly known. Objectives: The aim of this preliminary study was to evaluate the activity of angiotensin II receptor type (AGTR) 1 and 2 and lymphatic vessels in pulmonary patients with systemic sclerosis comparing with normal lung tissue (NLT) and with the extension of pulmonary fibrosis obtained from high-resolution computed tomography (HRCT) score. Methods: Lung specimens were obtained from 23 females patients (47±8.9yrs) with limited (n=10) and diffuse (n=13) SSc. NLT were obtained from 10 individuals (3 males and 7 females, 45±5.3yrs), who died suddenly of non-pulmonary causes. Immunohistochemistry and histomorphometry (point counting technique) were used to evaluate the amount of AGTR-1 and AGTR-2 pulmonary expression. Also we study the lymphatic (D2-40) expression and the percent of area occupied by these lymphatics in lung specimens. The pulmonary SSc compromising was evaluated by HRCT score. The association between the degree of HRCT parenchymal fibrosis, amount of AGTR-1, AGTR-2, lymphatic and dilatation area of lymphatics and pulmonary function tests was also considered. Results: We observed higher amount of AGTR-1 (11.41±6.97) and AGTR-2 (12.77±7.33 expression in the pulmonary parenchyma of patients with SSc when compared with NLT (2.95±1.98; 1.69±2.02, respectively) group, (p>0.01). The density of lymphatic vessels was markedly reduced in SSc (1.70±0.11) when compared with NLT (2.42±0.24, p=0.02) group. Similar situation was observed when we compared the area occupied by these lymphatics. The lymphatic area was minor in SSc (2.77±0.22) than in NLT (4.53±0.60, p=0.001) group. The HRCT score divided the SSc patients in two groups. The patients with minimal and severe fibrosis showed similar amount of AGTR-2 and lymphatic density. The patients with several fibrosis showed a increased expression of AGTR-1 (7.11±3.39) and increased area occupied by lymphatic (3.52±0.32) than minimal fibrosis (16.14±6.59; 2.19±0.1, respectively, p<0.05) patients. The increased of lymphatic area occupied had a negative association with VC (r=-0.633, p=0.008), FVC (r=-0.406, p=0.04) and DCO (r=-0.610, p=0.01). Conclusions: In conclusion, our data show that the AGRT-1 and AGTR-2 and lymphatic system is markedly affected in pulmonary SSc. The AGTR-1 showed higher expression in more pulmonary fibrosis HRCT score similar situation was observed with rarefaction of lymphatic vasculature was correlated with the degree of pulmonary fibrosis and pulmonary function test. The role in the evolution and in the clinical manifestations of the AGTR-1 principally and lymphatics is provably very important in the pulmonary progression and futures studies are necessaries. Financial Support: FAPESP, CNPq Disclosure of Interest: None Declared